(untitled) (Research, Society and Development, 2021)
Introduction: Palliative care underlies the daily life of health services, due to the increased burden of chronic diseases and aging. While teaching is fundamental, there are significant gaps in the medical curriculum. There is a consensus about the relevance of teaching in undergraduate courses; however, many schools do not include it in the curriculum. Methods: The search strategy was used, and descriptors were defined as follows: “palliative care” AND “medical education” OR “curriculum and competence clinical”, total of 89 papers were identified. From this sample, 67 papers were not included and 22 papers analyzed. Results: The emerging categories were as follows: impact on learning by the incorporation of palliative care education in the undergraduate medical course, essential competencies in palliative care in the medical undergraduate course and obstacles and paths aimed at its insertion in the undergraduate medical curriculum. Disciplinary modules contribute to changes in the approach to finitude and the acquisition of emotional competencies by professionals. This paper addresses a systematic review of how and why palliative care teaching should be carried out in graduation, considering difficulties and challenges for curricular incorporation. The main obstacles identified were lack of clinical context for education, lack of curricular time in the face of the demand, low support and structure, lack of qualified teachers, fragmented teaching and formal absence in curricula. Conclusion: The studies analyzed demonstrate benefits of teaching in PC in medical training, through longitudinal education, since they enhance the acquisition of essential skills in the exercise of medicine and especially in the treatment of people with life-threatening diseases.